2016
DOI: 10.1111/evo.12854
|View full text |Cite
|
Sign up to set email alerts
|

The Red Queen lives: Epistasis between linked resistance loci

Abstract: A popular theory explaining the maintenance of genetic recombination (sex) is the Red Queen Theory. This theory revolves around the idea that time-lagged negative frequency-dependent selection by parasites favors rare host genotypes generated through recombination. Although the Red Queen has been studied for decades, one of its key assumptions has remained unsupported. The signature host-parasite specificity underlying the Red Queen, where infection depends on a match between host and parasite genotypes, relie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
56
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(62 citation statements)
references
References 49 publications
6
56
0
Order By: Relevance
“…Importantly, spore attachment is genetically determined and fully consistent with infection success, i.e. resistant host genotypes prevent spore attachment whereas attachment is successful in susceptible host genotypes [1922]. Here we use the terms resistance and susceptibility to refer to both spore attachment and overall infection.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, spore attachment is genetically determined and fully consistent with infection success, i.e. resistant host genotypes prevent spore attachment whereas attachment is successful in susceptible host genotypes [1922]. Here we use the terms resistance and susceptibility to refer to both spore attachment and overall infection.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous hypotheses have been proposed to explain how the benefits of sex may outweigh its costs (see refs. 3 and 5 for reviews) and, although studies have provided tests of core assumptions (6,7) or found evidence consistent with theory (8)(9)(10), direct experimental evidence of sex evolving within populations remains rare (but see refs. 11 and 12).…”
mentioning
confidence: 99%
“…that this genetic host-parasite match involves several linked resistance loci, remained unsupported so far. Metzger and coauthors [1] now provide empirical support for it. Daphnia magna can reproduce both sexually and clonally and their well-studied interaction with Pasteuria ramosa makes them an excellent model system to investigate the genetics of host resistance.…”
mentioning
confidence: 87%
“…D. magna hosts were found to be either resistant (complete lack of attachment of parasite spores to the host's foregut) or susceptible (full attachment). In this study the authors carried out an elegant Mendelian genetic investigation by performing multiple crosses between four host genotypes differing in their resistance to two different parasite isolates [1]. Their results show that resistance of D. magna to each of the two P. ramosa isolates relies on Mendelian inheritance at two loci that are linked (A and B), each of them having two alleles with dominant resistance; furthermore resistance to one parasite isolate confers susceptibility to the other.…”
mentioning
confidence: 99%